Can an EASYcare based dementia training programme improve diagnostic assessment and management of dementia by general practitioners and primary care nurses? The design of a randomised controlled trial - Lucassen PL; van Eijken MIJ; Borm GF; van Achterberg T; Drašković I; Perry M; Vernooij-Dassen MJFJ; Olde Rikkert MGM (BMC, 2008)
Abstract Background Early diagnosis of dementia benefits both patient and caregiver. Nevertheless, dementia in primary care is currently under-diagnosed. Some educational interventions developed to improve dementia diagnosis and management were successful in increasing the number of dementia diagnoses and in changing attitudes and knowledge of health care staff. However, none of these interventions focussed on collaboration between GPs and nurses in dementia care. We developed an EASYcare-based Dementia Training Program (DTP) aimed at stimulating collaboration in dementia primary care. We expect this program to increase the number of cognitive assessments and dementia diagnoses and to improve attitudes and knowledge of GPs and nurses. Methods The DTP is a complex educational intervention that consists of two workshops, a coaching program, access to an internet forum, and a Computerized Clinical Decision Support System on dementia diagnostics. One hundred duos of GPs and nurses will be recruited, from which 2/3 will be allocated to the intervention group and 1/3 to the control group. The effects of implementation of the DTP will be studied in a cluster-randomised controlled trial. Primary outcomes will be the number of cognitive assessments and dementia diagnoses in a period of 9 months following workshop participation. Secondary outcomes are measured on GP and nurse level: adherence to national guidelines for dementia, attitude, confidence and knowledge regarding dementia diagnosis and management; on patient level: number of emergency calls, visits and consultations and patient satisfaction; and on caregiver level: informal caregiver burden and satisfaction. Data will be collected from GPs' electronic medical records, self-registration forms and questionnaires. Statistical analysis will be performed using the MANOVA-method. Also, exploratory analyses will be performed, in order to gain insight into barriers and facilitators for implementation and the possible causal relations between the rate of success of the intervention components and the outcomes. Discussion We developed multifaceted dementia training programme. Novelties in this programme are the training in fixed collaborative duos and the inclusion of an individual coaching program. The intervention is designed according to international guidelines and educational standards. Exploratory analysis will reveal its successful elements. Selection bias and contamination may be threats to the reliability of future results of this trial. Nevertheless, the results of this trial may provide useful information for policy makers and developers of continuing medical education. Trial registration ClinicalTrials.gov ID NCT00459784